(untitled) (Świat Idei i Polityki, 2014)
In Europe, there we have 12 monarchies, of which 11 are Member States of the Venice Commission (European Commission for Democracy through Law), which is responsible for issuing opinions on constitutional amendments and advising on matters of constitutional law. The article is an attempt to create a synthetic model of monarchy, which is the result of the opinions and comments of experts of the Venice Commission. First of all, on the basis of opinions on constitutional amendments in both: Liechtenstein and Luxembourg, the author is trying to point out what rules standing at the foundation of modern European monarchy are highlighted by the experts of the Commission.